Corrigendum - Alessandro De Gloria (Serious Games Society, 2015)
The paper "State-of-the-art in Business Games", by Petridis P. et. al., published in IJSG Vol 2, No 1 did not cite the paper "The Use of Serious Games in the Corporate Sector. A State of the Art Report", Learnovate Center, December 2012 , by Donovan L. This is the corrigendum.